Measuring the networked nonprofit : using data to change the world - Kanter, Beth, 1957-; Delahaye Paine, Katie, 1952-; Paarlberg, William T. (San Francisco, California : Jossey-Bass, A Wiley Imprint, 2012)
'The tools nonprofits need to measure the impact of their social media. Having a social media measurement plan and approach can no longer be an after-thought. It is a requirement of success. As nonprofits refine their social media practice, their boards are expecting reports showing results. As funders provide dollars to support programs that include social media, they too want to see results. This book offers the tools and strategies needed for nonprofits that need reliable and measurable data from their social media efforts. Using these tools will not only improve a nonprofit's decision making process but will produce results-driven metrics for staff and stakeholders. A hands-on resource for nonprofit professionals who must be able to accurately measure the results of their social media ventures. Written by popular nonprofit blogger Beth Kanter and measurement expert Katie Delahaye Paine. Filled with tools, strategies, and illustrative examples that are highly accessible for nonprofit professionals. This important resource will give savvy nonprofit professionals the information needed to produce measurable results for their social media'--
Includes bibliographical references (page 287) and index.
Keywords: Nonprofit organizations; Social networks